Make discovery through serendipity: a generative design platform for performative architectural design exploration - Indraprastha, Aswin (Universitas Gadjah Mada, 2024)
The repercussions of information technologies in the design process are undoubtedly revolutionary. As the digital natives will no longer require a traditional method to learn digital tools in architecture, there is a need to shift from tradition-bound techniques to an experimental mode where creativity and innovation rely upon a platform of explorative, speculative, and the recognition of serendipity and error as a credible basis on which innovation occurs. This study seeks to embrace a new method for design exploration by a generative design platform. Form-finding is encouraged through a bottom-up process of speculative actions. The goal is to cultivate serendipitous discoveries in the design process and leverage generative tools to explore performative aspects of architecture. The findings of this research offer some insights into how generative design platforms can encourage performative architectural design exploration.